Building counting by traditional game: Mathematics Program for Young Children - Nasrullah, Nasrullah; Zulkardi, Zulkardi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
In line with design research, the use of Bermain Satu Rumah (BSR) asÃ‚Â traditional Ã‚Â game to support childrenÃ¢â‚¬â„¢s counting classroom whereinÃ‚Â students are encouraged to construct mathematical understanding.Ã‚Â Number in traditional games is an interesting aspect that is helpful forÃ‚Â children to encounter numerous situations that bring them into contactÃ‚Â with sounds, symbols and meanings that relate to numbers. BermainÃ‚Â satu rumah as starting activity would be media to enhance studentÃ¢â‚¬â„¢sÃ‚Â sense of number as well as to be used as learning material. ByÃ‚Â developing Ã‚Â model-of Ã‚Â problem of bermain Ã‚Â satu rumah as traditionalÃ‚Â context, resultative counting is counting a number of things with theÃ‚Â aim of determining how many are there (the result) that can be showedÃ‚Â by using addition and multiplication concepts. StudentÃ¢â‚¬â„¢s thinking onÃ‚Â their level exhibited us their successful conservation when they were inÃ‚Â the last grade. The progress of understanding by game, especiallyÃ‚Â bermain Ã‚Â satu Ã‚Â rumah, is concrete effort to support number learning inÃ‚Â primary school. Using game in learning process, for instance, mathematics learning for primary school can be a mathematics programÃ‚Â for young children.